Synthesis of Triply Fused Porphyrin‐Nanographene Conjugates. (1st August 2018) - Chen, Qiang; Brambilla, Luigi; Daukiya, Lakshya; Mali, Kunal S.; De Feyter, Steven; Tommasini, Matteo; Müllen, Klaus; Narita, Akimitsu
Abstract: Two unprecedented porphyrin fused nanographene molecules, 1 and2, have been synthesized by the Scholl reaction from tailor‐made precursors based on benzo[ m ]tetraphene‐substituted porphyrins. The chemical structures were validated by a combination of high‐resolution matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (HR MALDI‐TOF MS), IR and Raman spectroscopy, and scanning tunnelling microscopy (STM). The UV‐vis‐near infrared absorption spectroscopy of1 and2 demonstrated broad and largely red‐shifted absorption spectra extending up to 1000 and 1400 nm, respectively, marking the significant extension of the π‐conjugated systems.